A Symbiosis of Multi-Criteria Decision Making and Electroencephalography: A Review of Techniques, Applications, and Future Directions - Aylin Adem; Erman Cakit; Metin Dagdeviren; Anna Szopa; Waldemar Karwowski (IEEE Access)
Multi-criteria decision-making (MCDM) problems are generally oriented toward strategic decisions and have a significant economic aspect, holding a special place in decision-making processes. To address these problems, specialized techniques have been developed and utilized. Electroencephalography (EEG) is a technique that measures brain activity, and the results can be used both to diagnose neurological disorders and to create more productive and healthier working conditions in a wide variety of areas. This paper discusses the collaborative nature between MCDM and EEG, focusing on how EEG and MCDM processes can enhance each other. Based on the database search results, thirty-five out of 149 papers were selected for the review process. By examining the literature on both macro and micro scales, the following were mainly retrieved: a) the MCDM techniques applied and their use in analyzing EEG data, b) EEG devices and wave types used in the MCDM process, c) the attributes of MCDM or EEG that were focused on, and d) current trends in knowledge and research opportunities. The results of this study will help identify potential future research areas, as well as provide a comprehensive overview of the existing literature. To summarize the findings, it can be concluded that EEG measurements of decision-makers’ cognitive states during the application of MCDM techniques improve the MCDM process and the presentation of these techniques, or they enhance the results obtained by MCDM based on the cognitive states of decision-makers when evaluating alternatives. Additionally, MCDM techniques contribute to improvements in the classification or feature extraction stages of data obtained through EEG.